2020
DOI: 10.1002/elan.202060341
|View full text |Cite
|
Sign up to set email alerts
|

Nickel Selenide Quantum Dot Applications in Electrocatalysis and Sensors

Abstract: Quantum dots (QDs) are semiconducting materials with diameters ranging from 2-10 nm. Amongst these QDs, nickel selenide quantum dot (NiSeQD) materials have gained much interest from researchers over the past few years due to their outstanding properties. These include excellent catalytic activity, good electrical conductivity for charge transfer, and excellent thermodynamic stability. NiSeQD material is relatively cheap, less toxic, and can be synthesised easily. Due to the fascinating and remarkable propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 123 publications
(220 reference statements)
0
4
0
Order By: Relevance
“…The azo bonds (-N=N-) in the dye molecule are destroyed during the CR reduction process, resulting in a variety of aromatic amine derivatives. Abolanle et al, 2020 noted a constant decline in the absorption band strength at 498 and 348 nm as time progressed and the colour changed from radish brown to colourless ( Tito et al, 2020 ). The link between ln (A t /A 0 ) and response time was discovered to be linear.…”
Section: Resultsmentioning
confidence: 99%
“…The azo bonds (-N=N-) in the dye molecule are destroyed during the CR reduction process, resulting in a variety of aromatic amine derivatives. Abolanle et al, 2020 noted a constant decline in the absorption band strength at 498 and 348 nm as time progressed and the colour changed from radish brown to colourless ( Tito et al, 2020 ). The link between ln (A t /A 0 ) and response time was discovered to be linear.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, transition metal Ni-based compounds concerning (oxy)­hydroxides, carbides, sulfides, phosphides, selenides, and nitrides have been extensively established as alternatives for noble metal electrocatalysts. In particular, nickel selenide materials with rich valence states are more eye-catching than their counterparts due to their exceptional aptitudes embodying cost-effectiveness, metallic nature, and adjustable electronic structure. Nevertheless, as burgeoning electrocatalysts, nickel selenides are far from having a satisfactory catalytic performance for full water splitting owing to their poor intrinsic activity and insufficient exposure to active sites. With regard to the HER process, pioneering evidence has demonstrated that the Se atom in nickel selenides acts as an active site to promote hydrogen production, but the weak binding energy between Se and adsorbed hydrogen (H ads ) hampers water decomposition that provides the H ads species, resulting in sluggish kinetics toward HER. Compared to the activity of HER, the efficient OER process is more difficult to activate in nickel selenides due to their supernal overpotentials and kinetic limitations. Concerning these above-mentioned issues, incorporating some transition metal dopants is expected to optimize the electron structure for assembled catalysts, thereby accelerating the water electrolysis process.…”
Section: Introductionmentioning
confidence: 99%
“…Ni@CDs have been synthesized by hydrothermal route using ethylene glycol, 3mercaptopropionic acid (MPA), ethylenediamine, vitamin-C (ascorbic acid, AA), polytetrafluoroethylene (PTFE) as carbon sources, and nickel chloride hexahydrate (NiCl2.6H2O) as salt. In this method, the temperature range is 180-200 ºC (14). This methodology had been used by various researchers for the synthesis of Ni@CDs.…”
Section: Solvothermal (Hydrothermal)mentioning
confidence: 99%
“…QDs have advantageous electrical and surface properties. The charge-transfer mechanism, which is principally used for the composite materials' super-capacitive capabilities, has been improved by the addition of QDs to the NiS matrix (13,14).…”
Section: Quantum Dots In Super-capacitormentioning
confidence: 99%